From the 2001 Evidence Regulation to its 2020 Recast: What does it remain and has it changed? - Santaló Goris, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
When courts of EU Member States have to take evidence in other Member States in the context of a civil or commercial procedure, they can rely on the 2020 Evidence Regulation. This instrument is the recast of the 2001 Evidence Regulation, and it provides two different paths for courts to take evidence abroad. One consists of a court asking a court in another Member State to take evidence on its behalf. This is the so-called indirect taking of evidence system. Alternatively, courts also have the possibility of directly taking the evidence located in another Member State. In broad terms, the 2020 Evidence Regulation has retained the main structure and content of the 2001 Evidence Regulation. However, it has introduced some innovations, such as the future mandatory use of electronic communications between the courts and authorities involved in the application of this instrument.